If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(4x + -2) = -112 Reorder the terms: -8(-2 + 4x) = -112 (-2 * -8 + 4x * -8) = -112 (16 + -32x) = -112 Solving 16 + -32x = -112 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16' to each side of the equation. 16 + -16 + -32x = -112 + -16 Combine like terms: 16 + -16 = 0 0 + -32x = -112 + -16 -32x = -112 + -16 Combine like terms: -112 + -16 = -128 -32x = -128 Divide each side by '-32'. x = 4 Simplifying x = 4
| (x+3)2=10 | | 0.5x^2-8=0 | | -3p+4(2-3p)=5 | | 4x^5+4x^4-9x^3-11x^2+x+3=0 | | 6x-9=-15x-9 | | 2x^2+x-150=0 | | 7(x+2(x-1))=3x | | 1x+4=15 | | 3x+0.28x=-8.82 | | 4x^2+29x+7=0 | | A=-4(8x-3)+6(-5x+3) | | =X^2-1 | | 6a^5+61a^3b^2+10ab^4=0 | | m+(2m+5.2)=41.8 | | 2x+2(2x-42)=228 | | -5+95x-90x^2=0 | | h=rt-256t | | -5x^2+14x+3=0 | | 2x^2+x-45=0 | | 81p^4-36p^3+4p^2=0 | | -15x^2+46x-35=0 | | 9x-14*5x+38= | | 10x^2=-21x+10 | | 7a^3b^3-63ab^3=0 | | 19-9x=7-4x | | 3(x-4)+5x=2(x-1)+3 | | A=-4(8x-3) | | 6=-8+6(y+3) | | 6x^4+27x^3y-15x^2y^2=0 | | A=(-4)*8x | | -5(-2x-2)+6x=-7x | | 4y^3-14y^2-98y=0 |